Wnt3a promotes epithelial–mesenchymal transition, migration, and proliferation of lens epithelial cells - Bao, Xiu-li (Molecular Vision, 2012)
PURPOSE: Posterior capsular opacification (PCO) is caused mainly by the epithelial–mesenchymal transition (EMT), proliferation, and migration of human lens epithelial (HLE) cells. wingless (Wnt) signaling has been implicated in the fibrotic process by inducing EMT and increasing the proliferation of epithelial cells. This study investigated the role of Wnt3a in PCO formation. METHODS: Wnt3a was overexpressed in the HLE B-3 cell line by transfected Wnt3a-pcDNA3 plasmid. The expressions of Wnt/β-catenin signaling component proteins, including β-catenin, E-cadherin, fibronectin, c-Myc, and cyclin D1, were detected by western blot analysis and immunocytofluorescence to confirm the efficiency of transfection efficiency and analyze the effects of overexpression. HLE migration ability was evaluated by transwell migration and wound healing assays, whereas HLE proliferation was analyzed by MTT [3-(4,5-dimethylthiazol-2-yl) −2,5-diphenyltetrazolium bromide] assay and flow cytometry. RESULTS: Overexpression of Wnt3a resulted in upregulated expression of β-catenin, c-Myc, and cyclin D1. Expression of the lens epithelial marker E-cadherin was down-regulated in Wnt3a-overexpressing HLE B-3 cells, whereas that of the mesenchymal marker fibronectin was upregulated. In addition, the morphology of HLE B-3 cells changed from the classic spindle shape to an irregular form. Overexpression of Wnt3a could enhance the ability of migration as determined by transwell migration and wound healing assays as well as promoted the proliferation of HLE B-3 cells by MTT assay and flow cytometry analysis. CONCLUSIONS: Wnt3a can induce EMT, migration, and proliferation of HLE cells and may be a valuable therapeutic target for the prevention and treatment of PCO.